Evaluation of the burns model for nitrate movement in wet sandy soils - Yusop, Mohd Khanif; Van Cleemput, Oswald; Baert, Leen (Blackwell Scientific Publications, 1984)
A simple model to predict nitrate leaching developed by Bums (1974) was tested. The measured and calculated nitrate concentrations in 100'cm wet sandy soil profiles were compared: the results showed reasonably good agreement between the two values. Adjusting the initial conditions and reducing the segment size from 10 to 5 cm did not improve the accuracy of the prediction. Better agreement was, however, obtained when only the samples above the groundwater table were considered.